The Effects of Student Teams Achievement Division (STAD) on Motivation of Saudi EFL Adult Learners - Ishtiaq, Muhammad; Zuraina, Ali; Salem, Muhammad (Universiti Malaysia Pahang, 2015)
Students Teams Achievement Division (STAD) is a cooperative learning strategy in which learners work in heterogeneous groups to achieve a common goal. It has been widely used in teaching different subject areas under different settings. This study aimed at investigating the effects of STAD on motivation of Saudi EFL learners. Two intact groups of 1st semester students were selected. One group worked as the experimental group and the other one as the control group. A questionnaire was administered to both groups at the beginning of the semester. The experimental group was taught with STAD whereas the control group was taught with the traditional whole class teacher-fronted method. The treatment was administered for two weeks. The same questionnaire was re-administered after the treatment. The data was analyzed using independent samples t-test. Findings revealed that there was no significant difference (p= 0.36> 0.05) between the experimental and the control groups in terms of motivation.